Quality evaluation of waffles produced from the partial replacement of wheat flour with green banana flour and potato starch [pdf] - Tran Ngoc Giau; Nguyen Minh Thuy; Vo Quoc Tien; Ngo Van Tai (My University, 2023)
Waffles have gradually become a common dish amongst Vietnamese people in recent years.However, carbohydrate-rich foods often have a high glycemic index (GI) and are not recommended for people with diabetes (Choi et al., 2009).White wheat flour is also a major ingredient in waffle making, so waffles are known to be a high GI product.For example, the GI database shows that waffles prepared with refined wheat flour have a mean GI of 76 (high GI as classification) (Chandra, 2020).Substituting it with other flours can reduce the glycemic index of waffles, making them useful for the prevention and management of type II diabetes and other associated diseases.Since the introduction of other flours into waffle production,
Keywords: Potato starch; Food composition and properties